Scenario Planning for Future Development of Rural Areas in Iran: Case of Rural Areas Around the City of Varzegan - Samadi, Lachin (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
Development in rural areas is affected by internal and external factors. These factors are making the structure of the system within which decisions are made. Since the policies and decisions adopted in rural plans affect the process of development in the rural areas, the role of them has been considered in the future of rural areas in Iran. Different scenarios and options have been suggested with the use of GIS to clarify the future outcome of these decisions. This study selected three rural areas around the city of Varzegan to consider the effect of both internal and external factors in the future of these areas. Internal factors directly influenced by the independent variable (Population Growth Rate suggested in rural plans), while external factor is beyond the control of it and affects it. Scenario sets shows that the rural area’s sustainability is affected by the population growth rate (actor of the structure), the damages in agricultural lands and employment composition. This fact is not considered in rural plans of Iran because of the need for residential areas due to reverse migration.